2017
DOI: 10.1037/fam0000316
|View full text |Cite
|
Sign up to set email alerts
|

Sexual orientation and future parenthood in a 2011–2013 nationally representative United States sample.

Abstract: Previous researchers have found evidence for differences in parenting goals between lesbian and gay people and their heterosexual peers. However, no previous research has quantified the parenting goals of bisexual people or evaluated parenting goals as a function of sexual partner gender. In addition, political and social climates for sexual minority people had improved rapidly since the last representative data on lesbian and gay peoples' plans for parenthood were collected. We analyzed data from 3,941 childl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
97
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(133 citation statements)
references
References 25 publications
17
97
6
1
Order By: Relevance
“…Gates et al 2007) our findings here must be interpreted with caution. In this regard is important to look at Riskind and Tornello's (2017) results. These authors found that bisexuals were more similar to heterosexuals than to lesbians and gay men in terms of their parenting desires and intentions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gates et al 2007) our findings here must be interpreted with caution. In this regard is important to look at Riskind and Tornello's (2017) results. These authors found that bisexuals were more similar to heterosexuals than to lesbians and gay men in terms of their parenting desires and intentions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, lesbians and gay men have also reported lower levels of both parenting desire and parenting intention compared with their heterosexual peers (Baiocco and Laghi 2013;Riskind and Patterson 2010). As for bisexual persons, previous studies have indicated more similarities in their attitudes to heterosexuals than to lesbians and gay men (Riskind and Tornello 2017). However, Simon et al (2018) recently found no differences concerning parenting desires and intentions among lesbians, bisexuals and heterosexual women.…”
Section: Impact Of Sexual Identity On Attitudes Toward Parenthoodmentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, given the history of legal restrictions, some LGBQ people sought to legitimize their families in other ways without relying on the law. Moreover, not all LGBQ individuals want to become parents (Riskind & Patterson, ; Riskind & Tornello, ) and the law is not the only factor in shaping decisions about parenthood (Mezey, ). It is, however, important for attorneys to be cognizant of the degree to which the law has played a role in both restricting LGBQ people's ability to pursue parenthood and in affecting LGBQ people's experiences of becoming parents.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, many gay men want to become parents in the future (Gates et al, 2007;Goldberg et al, 2012;Scandurra et al, 2019). Yet little is known about the decision-making process of childfree gay men toward becoming parents in the future (Mezey, 2013;Gato et al, 2017;Riskind and Tornello, 2017;Scandurra et al, 2019). The present study focuses on the parenting intentions of childfree gay men, compared to their lesbian and heterosexual peers.…”
Section: Introductionmentioning
confidence: 99%